EXPERIENCE IN DEVELOPING ANTI CRISIS PLAN FOR MORTGAGE BORROWERS - A. G. Semeniuk; A. A. Tsyganov; A. D. Yazykov (Стратегические решения и риск-менеджмент)
This article analyzes the experience in the development and implementation of anti-crisis plan for mortgage borrowers in 2009–2011. The plan is considered anticrisis measures, developed with the direct participation ARHML authors. The Plan includes both measures of a preventive character, aimed at informing potential distressed mortgage borrowers of the state program to support borrowers and activities to respond rapidly in the event of a sharp increase in the number of unemployed people in a particular region.